Eco-innovation impacts on recycled product performance and competitiveness: Malaysian automotive industry - Fernando, Yudi; Tseng, Ming-Lang; Sroufe, Robert; Abideen, Ahmed Zainul; Muhammad Shabir, Shaharudin; Jose, Rajan (Elsevier Publisher, 2021)
This study aims to develop a theoretical circular economy model that examines the impact of eco-innovation practices on recycled product performance and competitiveness in Malaysian automotive industry. The supply of recycled materials has been recognized as one of the critical components to produce brand new automotive products. This empirical study was conducted among automotive firms and groups consisting first, second, and third-tier suppliers. The data were analysed using structural equation modeling. The results support the importance of innovation and cost efficiency from the perspective of resource-based view and the ability of a firm to manage resources while practicing circular economy initiatives, whilst instrumental to the success of recycled product performance and competitiveness. The degree of competitiveness that a firm experiences through new product development is targeted by integrating the theory of resource-based view, eco-innovation, and circular economy. The findings reveal that eco-innovation practices with circular economy principles assist business competitiveness in the automotive industry.